The exploratory and confirmatory factor analysis for supervisory input support as the determinant of effective supervision in technology and engineering education - Ismail, Affero; Hassan, Razali; Masek, Alias; Nordin, Abdul Sukor; Jalani, Noor Hisham (Medwell Jommls, 2017)
This study investigates the predictors of Supervisory Input Support (SIS) for effective supervision. This element is analyzed for the practical implementation of effective supervisory practice for students in technology and engineering education. There are reports regarding supervision issue during their final year project supervision which requires a great and informative input from their supervisors. A sample of 360 students completed survey including measures of Management Input, Interpersonal Input, Academic Input, Project Input and Technical and Innovation Input. The sample was selected through stratified random sampling. All factor loading were set to be >0.6. An exploratory analysis was conducted and Structural Equation Modeling (SEM) was employed to investigate the Confirmatory Factor Amlysis (CF A) for SIS. The Goodness of Fit (GOT) was in good condition and the final model is proposed. This study introduces the elements that mormting the frmction of SIS. This study clarifies that the supports needed by students are different from one to another. If the supervisor could cater these challenges by providing effective inputs, the supervision process may enhance the supervision activity.